The Relationship between Monetary Policy and the Stock Market Cycle: An Empirical Study in Vietnam - Tran, Nhung Thuy (The Indonesian Capital Market Review, 2024)
The study examines the relationship between monetary policy and the stock market cycle in Vietnam. Using data from 2007 to 2022 and employing a VAR model, we estimate the impact of monetary policy factors on stock market cycle variables. The findings confirm a two-way causal relationship between monetary policy and the stock market cycle. However, the influence of cyclical fluctuations on the monetary policy transmission mechanism is weak, exhibits a lag, and predominantly occurs in the medium and long term. These results indicate that Vietnam's monetary policy requires time to absorb financial shocks and adjust to economic conditions. The study enhances the understanding of monetary policies in stock market regulation and provides evidence of its bidirectional nature concerning the market cycle.